A Highly Active Rh@Pd Nanocube Catalyst for Methanol Electrooxidation. Issue 10 (31st May 2021) - Yang, Sufang; Yang, Xiaobo; Tong, Xili; Yang, Nianjun
Abstract : The performance of direct methanol fuel cells (DMFC) is limited by the sluggish methanol oxidation reaction (MOR). Novel electrocatalysts are thus highly desired to boost the MOR. Herein, the morphology and composition of a bimetallic catalyst with a core–shell structure are thus tuned to realize improved MOR performance. On the Rh@Pd nanocube electrocatalyst, synthesized by means of a wet chemical approach and a surfactant as a morphological regulator, efficient MOR is achieved within a potential range as wide as 0.362 V at a current density as high as 100 mA mgcat −1 . The catalytic activity reaches 608.5 mA mgRh −1 at the first oxidation peak of the MOR and 1487.8 mA mgPd −1 at the second oxidation peak of the MOR. This catalyst displays increased antipoisoning capacity toward CO and long‐term stability. The superior performance of this bimetallic core–shell catalyst is attributed to the electron transfer from the Rh core to the semicoated Pd shell. Such a strategy paves a new way to design, synthesize, and utilize metal catalysts and further to develop DMFCs on a large scale and probably for industrial applications. Abstract : A Rh@Pd nanocube catalyst with a core–shell structure is synthesized, exposing both Rh and Pd active sites on the catalyst surface for methanol electrooxidation. It thus exhibits high mass activity, excellent CO tolerance ability, and long‐term durability. Such superior catalytic activity is derived from the occurrence of electron transfer from the Rh core to the Pd shell.